Potential of phytopathogenic fungal isolates as a biocontrol agent against some weeds - Youssef M. M. Mohammed; Mohamed E. I. Badawy (Egyptian Journal of Biological Pest Control, 2020)
Abstract Bioherbicides afford satisfactory approach to overcome weed problem. Selection of new bioherbicides from phytopathogenic microbiota is essential for modern agricultural management, especially mycoherbicides. Thus, in the present investigation, 4 phytopathogenic fungi including Alternaria alternata YMM1, A. tenuissima YMM3, Chaetomium globosum YMM2, and Nigrospora oryzae YMM4 were isolated from infected leaves with chlorotic rings of Rumex dentatus and Sonchus oleraceus as common weeds in Egypt. These fungi were identified based on morphology and sequence analysis of ITS1-5.8SrDNA-ITS2 of rRNA genes. Mycoherbicidal metabolites were produced using submerged cultures in potato dextrose broth. Their bioherbicidal activities were evaluated using seed germination and leaf disk puncture assays. It was found that the most promising fungal strain against major tested weeds was N. oryzae YMM4. Thus, phytopathogenic microbiota are considered a great resource for the construction of a new bioherbicide for managing weeds.